Postpolypectomy prophylactic clip closure for the prevention of delayed postpolypectomy bleeding: A systematic review - Mangira, Dileep (JGH Open, 2018)
Delayed postpolypectomy bleeding (DPPB) is the most common complication of colonoscopic polypectomy. Prophylactic clipping after an uncomplicated polypectomy is increasingly used, but it is unclear if this results in the prevention of DPPB. This study aimed to review prophylactic clip use and its effect on the rates of DPPB. MEDLINE, Embase, and the Cochran Library were systematically searched for studies (1995–March 2017) that used prophylactic hemoclips and assessed DPPB as an outcome. Of 1402 articles identified, nine papers were eligible for inclusion, evaluating 4311 patients and 7783 polyps; 118 patients experienced a DPPB, and 49 of these patients received prophylactic clips. There was no significant difference in DPPB rates in patients who received prophylactic clipping compared to those who did not (odd ratio: 0.8; 95% confidence interval: 0.36–1.77; P = 0.56). There was also no significant difference in the DPPB of polyps <20 mm compared with polyps ≥20 mm. Clip application for prophylactic management of an uncomplicated polypectomy has not been demonstrated to reduce the risk of DPPB, casting doubt on the use of this costly practice.